The effect of gelatin as pore expander in green synthesis mesoporous silica for methylene blue adsorption - Ulfa, Maria (Scientific Reports, 2022)
Mesoporous silica NSG had been synthesized while employing gelatin as a natural template to successfully increase the particle size and expand the pore diameter of NSG. All silica samples exhibited a similar XRD pattern with a broad peak centred at 2θ = 22.9°, as the characteristic of amorphous silica. FTIR results showed that the reduction of Si–O–Si symmetric stretching vibrations at 1075 cm− 1 was due to the use of a high percentage of gelatin. Moreover, TEM analysis displayed the mesoporous channels in the form of a honeycomb structure with a diameter of ± 6 nm. Gelatin enhanced the surface area of silica from 467 to 510 m2/ g, the pore volume from 0.64 to 0.72 cc/g and expanded the pore diameter from 3.5 nm to 6.0 nm. The expansion of the ordered mesopores with the increase of P123: gelatin ratios was elucidated by the pore size distribution. The adsorption capacity of methylene blue (MB) was improved on mesoporous silica with an expanded pore dimension to give 168 mg/g adsorption capacity within 70 min.